Accumulation of local defects in the zone of forced elasticity before the front of a failure crack in polymers - A. A. Valishin; T. S. Stepanova (Тонкие химические технологии)
This article is dedicated to accumulation of local defects in the zone of forced elasticity before the front of a failure crack in polymers. The mechanism of microcavity formation in the crack and the mechanism of the break-up of loose junctions in the support framework were described. The kinetic equation of the break-up of loose junctions in the support framework was obtained, and the junction break-up time was calculated.